Adhesion and adhesives technology : an introduction - Pocius, Alphonsus V.; Smith, Mark (Cincinnati : Hanser Publications, 2021)
"This book describes, in clear understandable language, the three main disciplines of adhesion technology: 1) mechanics of the adhesive bond, 2) chemistry of adhesives, and 3) surface science. Some knowledge of physical and organic chemistry is assumed, but no familiarity with the science of adhesion is required. The emphasis is on understanding adhesion, how surfaces can be prepared and modified, and how adhesives can be formulated to perform a given task. Throughout the book, the author provides a broad view of the field, with a consistent style that leads the reader from one step to the next in gaining an understanding of the science. The 4th edition has additional content covering sustainability (use of natural products in adhesives) and bonding of composite materials. There are also updates and small improvements throughout, together with some new review questions aprovided at the end of the chapters. Contents: - Introduction - Mechanical Properties of Materials as They Relate to Adhesives - Mechanical Tests of Adhesive Bond Performance - Basics of Intermolecular Forces and Surface Science - Basic Physical/Chemical Properties of Polymers - Relationship of Surface Science and Adhesion Science - Surface Preparation of Adherends for Adhesive Bonding - Chemistry and Physical Properties of Structural Adhesives - Chemistry and Physical Properties of Elastomer-Based Adhesives - Thermoplastic, Pseudothermoplastic, and Other Adhesives - Basis for Adhesive Bond Design - Index"--